(untitled) (Journal of Pharmaceutical Negative Results, 2022)
During the Chola period women were treated as a valuable object and a precious metal. In times of war instead of giving them safe and security they were annexed as war booty along with other spoils of war and were transported to the home of the victorious party and then used for their filthy purposes. This practice was prevalent in the Tamil country even from the Sangam age. Araiyaninatheshwara Temple is the 44th Devara Paadal Petra Siva Sthalam on the north bank of Thenpennai River and 12th Sthalam Nadunadu. This place was called as Araiyaninallur during Devara times, has got corrupted to the present name of Arakandanallur. Chiefs also bore the title of Vanniyanayan (the Chief of the Vanniyas). Sarrukkudadan was a biruda one of these chiefs mentioned earlier bore, meaning ‘he who does not yield’. He would appear to have had very loyal and devoted servants and subordinates; this is borne out by the large number of brief records found in the temples containing vows made by them to the effect that they would die if their master died and not survive him.